Financial Consumer Protection in the Era of Digital Transformation: A critical survey of literature and policy practices - Cho, Man; Park, Soojin (KDI School of Public Policy and Management, 2021)
This study aims to shed light on how to foster a welfare-enhancing policy regime for financial consumer protection (FCP), mainly through a literature and institutional survey on three pillars of FCP policy - financial education, ex ante (or before point of sale) FCP measures, and ex post policy instruments. To that end, we first conceptualize the typical behavioral patterns in the demand- and supply-side of the financial markets, to be tamed through an FCP policy regime, and also attempt to reflect the ramifications of the on-going global trend of digital transformation. As to the first pillar, most of the literature claims that no consensus exists as to the goal of financial education (FE), one that is clear, specific, and measurable enough to guide empirical endeavor to gauge its effectiveness. On this issue, we suggest three dimensions of financial capability as possible targets of measuring the effectiveness of FE – knowledge dimension, choice and decision dimension, and outcome dimension, and discuss a possible testing strategy. Another issue stressed is that, given the inherent complexities in most financial products, the second letter “E,” i.e., pedagogy and timing, should be given a higher weight than the first one “F,” i.e., contents, in designing a FE strategy. In the supply-side, three sets of policy instruments are discussed as the key FCP elements: that is, the self-regulation mechanisms such as code of conduct, and training and certification programs for business ethics; the behavioral principles along with rules and regulations to ensure fair and ethical consumer treatment (FECT); and, internal governance structure to align FECT with incentives of employees of financial institutions. In addition, dispute resolution mechanism along with the legal responsibility of service providers if and when FECT is violated are also discussed. Using the key findings, we develop a template, or a checklist, by interacting the key behavioral patterns to be tamed with the FCP policy instruments, and suggest a set of indicators based on the matrix developed to be used for international comparison.
Keywords: Digital Transformation; Financial Consumer Protection; Financial Education; Conflict Resolution; Financial Consumer Policy